2011
DOI: 10.1364/josab.28.002735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface oxidation on the linear optical properties of Cu nanoparticles

Abstract: Applications of copper nanoparticles (NPs) are restricted due to their proneness to oxidation by ambient oxygen if not properly protected. Here we discuss the optical properties and application potential of copper NPs covered by a thin oxide layer. Considering Cu@Cu 2 O core-shell type structures with different core size and shell thicknesses, linear optical properties of surface-oxidized copper NPs have been studied theoretically. Contrary to common perception, it has been demonstrated that surface-oxidized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 47 publications
3
38
0
3
Order By: Relevance
“…Here, the oxidation behavior in solvent‐free conditions has been studied, but the oleic acid capping ligand may also serve to initially damp the plasmon resonance until a shell of Cu 2 O is formed . Theoretical studies of the linear optical properties of Cu@Cu 2 O core–shell nanostructures provide insight into the surface plasmon response of this oxidized system, and indicate that the plateau or rise in peak absorbance may also have a contribution from the shift of the LSPR peak to wavelengths outside of the region of the interband transitions of copper . At longer oxidation times, the plasmon peak absorbance decays rapidly until it reaches a constant absorbance upon complete Cu oxidation and the plasmon response disappears.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the oxidation behavior in solvent‐free conditions has been studied, but the oleic acid capping ligand may also serve to initially damp the plasmon resonance until a shell of Cu 2 O is formed . Theoretical studies of the linear optical properties of Cu@Cu 2 O core–shell nanostructures provide insight into the surface plasmon response of this oxidized system, and indicate that the plateau or rise in peak absorbance may also have a contribution from the shift of the LSPR peak to wavelengths outside of the region of the interband transitions of copper . At longer oxidation times, the plasmon peak absorbance decays rapidly until it reaches a constant absorbance upon complete Cu oxidation and the plasmon response disappears.…”
Section: Resultsmentioning
confidence: 99%
“…19 The observed B20 nm red-shift in the SPR band can be assigned to the presence of a Cu 2 O layer that affects the dielectric properties surrounding the metallic Cu core (Cu@Cu 2 O). [19][20][21] The NPs prepared in an oxidative environment were unstable, and were completely precipitated after a short period of time (B3 hours).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the SPR band suffers a decrease in intensity that depended on the thickness of the oxide layer, together with a red-shift in the SPR maxima. 21 The red-shift of the Cu NPs SPR to the near IR is an advantage, since it takes the resonance away from the region of interband transition. The presence of aggregates also red-shifts and broaden the SPR band.…”
Section: Short-circuit Current Density and External Quantum Efficiencmentioning
confidence: 99%
“…Cysteine was used as stabilizer agent to prevent the oxidation of Ag-Cu alloy nanoparticles. 18 However, Pal et al 38 reported that the plasmonic properties of Cu nanoparticles are enhanced on formation of small shell layer thickness of copper oxide on Cu nanoparticles. Therefore, the plasmonic properties of Ag-Cu alloy nanoparticles would also be expected to enhance due to the formation of Cu 2 O layer (Ag 0.50 Cu 0.50 @Cu 2 O).…”
Section: Resultsmentioning
confidence: 99%